POSITIVE DEVIANCE CASES ON SOCIAL FUNCTIONS OF ELDERLY WARIA (CASE STUDY ON THE ANAK RAJA WARIA SHELTER DEPOK, WEST JAVA) - Rabbani, Zaenoon; Imelda, Johanna Debora (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2021)
In developing societies, the elderly in Indonesia are generally cared for by their own families traditionally. However, that does not appear to the transgender community in their old age. The discrimination experienced by waria (transgender in Bahasa, red.) begins when they decide to follow their identity as a woman at an early age. During their lifetime, transgender women frequently get discrimination and rejection from the social environment, which causes them to be unable to function socially in a proper way. Fortunately, those experiences are not the case for elderly transgender who lives under the protection of Anak Raja Transgender Shelter established by the Indonesian Transgender Communication Forum (FKWI). This study examines how elderly transgender women in Anak Raja Transgender Shelter can function socially and be accepted by the environment. The case of positive deviance that occurs in elderly transgender women, in social science studies, is said as a case of Positive Deviance. This research is a qualitative study that applies in-depth interviews for data collection. The main informants are elderly transgender women who are more than 60 years old and have been under the protection of Anak Raja Waria Shelter for at least 1 year. Social functioning in the elderly is a multidimensional concept so that the assessment requires several things to be explored such as social support, social networks, social resources, social roles, role functioning, and social activities. This study found that elderly transgender women at the Anak Raja Waria Shelter can fulfill the five assessments because the strong social support comes from both the community itself and the social environment in where they live.